Inhalable and respirable dust concentration of soiled stone, metal and ceramic artefact inside National Museum Malaysia - Mohd. Din, Shamzani Affendy; Mat Husin, Nur Baiti; Othman, Rashidi (Malaysia Institute of Planners, 2018)
The airborne particulate matter is a key indicator of air pollution brought into the air by a variety of natural and human activities. As it can travel in distances and suspended in the atmosphere, it affects human health and museum artifact. The primary idea of this paper is to discuss the mass concentration of airborne particulates matter in terms of inhalable and respirable dust from the stone, metal and ceramic display showcase. The fluctuation of temperature and relative humidity, the museum cleaning activity, the usage of the HVAC system and construction activity affect the soiling defect of stone, metal and ceramic artifact. The approach selected to collect primary data for this research is by conducting a case study at the National Museum of Malaysia. Personal air sampling was conducted using Casella 7-Holes and Cyclone sampler head. Results revealed high abundances of inhalable dust at the stone and ceramic artifact both in Galley A and B. This study is beneficial towards the Jabatan Muzium Malaysia (JMM), Department of Environment (DOE), Ministry of Health (MOH) and Ministry of Natural Resources and Environment (MONRE) by emphasizing that reducing air pollution will reduce soiling defect of the museum artifact. Thus, it can reduce government expenses to the museum management towards cleaning procedure for the damaged artifact.